Overexpression of Lectin Receptor-Like Kinase 1 in Tomato Confers Resistance to Fusarium oxysporum f. sp. Radicis-Lycopersici - Yue, Zhi-Liang; Tian, Zhe-Juan; Zhang, Jun-Wei; Zhang, Sheng-Wei; Li, Ya-Dong; Wu, Zhi-Ming (Frontiers in Plant Science, 2022)
The disease Fusarium crown and root rot (FCRR), caused mainly by Fusarium oxysporum f. sp. radicis-lycopersici (FORL), seriously affects commercial tomato [Solanum lycopersicum (Sl)] yields. However, the genes that offer resistance to FORL are limited and the mechanism of resistance to FCRR is poorly understood. Lectin receptor-like kinases (LecRKs) play critical roles in defensive responses and immunity in many plant species; however, whether specific LecRKs are involved in the response of tomato plants to FORL is unclear. Here, we report that the expression of SlLecRK1/Solyc09g011070.1 was obviously induced by the infection of FORL. Biochemical and cell biological data revealed that SlLecRK1 is an active kinase that is located at the cell membrane, while real-time quantitative PCR data suggested that SlLecRK1 is mainly expressed in stems and roots. Genetic studies showed that overexpression of SlLecRK1 significantly improved the resistance of tomato plants to FORL but did not cause visible changes in plant growth and development compared with wild-type control plants. RNA-Seq data suggested that the positive effects of SlLecRK1 on the resistance of tomato plants to FORL occur mainly by triggering the expression of ethylene-responsive transcription factor (ERF) genes. Together, our findings not only identify a new target for the development of FCRR-resistant tomato varieties, they also demonstrate a molecular mechanism linking SlLecRK1 and ERFs in regulating the immune responses of tomato plants to FORL.